How relevant is copyright to online artists? A qualitative study of understandings, coping strategies and possible solutions - Dowthwaite, Liz; Houghton, Robert J.; Mortier, Richard (University of Illinois at Chicago Library, 2016)
Online copyright law is a major issue for many in the creative industries. Independent artists often rely on sharing their work across social media and content-sharing sites, leaving them open to having their work stolen or misused. This paper discusses a series of 11 semi-structured interviews that examined attitudes towards copyright and attribution amongst webcomic artists, in relation to current copyright laws across the EU and internationally. Whilst artists are generally aware of the cover provided by copyright, they feel that it is not necessarily relevant or effective within the creative space they work in. There is very little support and there are few resources available to help them to fight for control of their work, and whilst artists do get angry about actual theft and removal of attribution, they accept that they have to put up with certain violations if they wish to continue to publish comics for free on the Internet. The paper ends by discussing potential solutions to the problems raised.